2018
DOI: 10.1016/j.it.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Canonical and Non-Canonical Wnt Signaling in Immune Cells

Abstract: Cell differentiation, proliferation, and death are vital for immune homeostasis. Wnt signaling plays essential roles in processes across species. The roles of Wnt signaling proteins and Wnt ligands have been studied in the past, but the context-dependent mechanisms and functions of these pathways in immune responses remain unclear. Recent findings regarding the role of Wnt ligands and Wnt signaling in immune cells and their immunomodulatory mechanisms suggest that Wnt ligands and signaling are significant in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 114 publications
(153 reference statements)
0
111
0
Order By: Relevance
“…The results also discard the possibility that the presence of IL-36g changes the signaling pathway mediated by WNT5A leading to bacterial killing. In addition, JNK and NF-kB are downstream pathways of noncanonical WNT signaling pathway (19,29,30). Ours results showed that both rhIL-36g and rhWNT5A induced increased p-JNK and p-p65 ( Fig.…”
Section: Il-36g Mediated the Bactericidal Activity Partly Through Thementioning
confidence: 60%
See 2 more Smart Citations
“…The results also discard the possibility that the presence of IL-36g changes the signaling pathway mediated by WNT5A leading to bacterial killing. In addition, JNK and NF-kB are downstream pathways of noncanonical WNT signaling pathway (19,29,30). Ours results showed that both rhIL-36g and rhWNT5A induced increased p-JNK and p-p65 ( Fig.…”
Section: Il-36g Mediated the Bactericidal Activity Partly Through Thementioning
confidence: 60%
“…In this study, we confirmed that IL-36g suppresses M. tuberculosis growth in macrophages by triggering WNT5A-induced noncanonical WNT signaling-mediated autophagy. Our study revealed that IL-36g or WNT5A can activated the noncanonical WNT pathway by inducing JNK and p65 phosphorylation (19,29,30), although the specific downstream mechanisms are worthy to be studied. Furthermore, we have filled in the pathway of WNT5A-induced autophagy, verifying it was mediated by COX-2, a key rate-limiting enzyme in the arachidonic acid pathway, and subsequent inactivation of AKT/mTOR signaling.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Genes regulated by Yap include several key effectors of T cell activation, including those controlling JAK-STAT signaling that modulate the polarization of naïve CD4s into T helper subsets (Seif et al, 2017). Notably, Yapregulated genes are also enriched for those regulated by the TGFb and Wnt pathways, which have important pleotropic roles in T cell biology (Batlle and Massague, 2019;Chae and Bothwell, 2018). Given the known convergence of Yap with these immunomodulatory pathways (Varelas and Wrana, 2012) it is likely Yap directs their transcriptional targets and signal strength.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ZEB2 is involved in T cell differentiation (Goossens et al, 2019) and neurological development (Epifanova et al, 2018). LEF1 is important during osteogenesis (Li et al, 2018), immune cell regulation (Chae and Bothwell, 2018), and hair follicle development (Abaci et al, 2018). ETS1 is an important regulator of lymphatic cell differentiation and physiology (Garrett-Sinha et al, 2016).…”
Section: Robustness Analysismentioning
confidence: 99%